2016
DOI: 10.9767/bcrec.11.3.571.316-329
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Methacrylate and Alpha-Methyl Styrene: New Strategy for Synthesis of Bloc Copolymers for Use in Potential Biomedical Applications Generated by an Ecologic Catalyst Called Maghnite (Algerian MMT)

Abstract: A new model for synthesis of the plastics, block copolymers were prepared from methyl methacrylate (MMA) and alpha-methyl styrene (α-MS) by cationic copolymerization in the presence of a new and efficient catalyst of "Maghnite-Na" at 0 °C in bulk. In this paper, the copolymerization of α-MS and MMA was induced in heterogeneous phase catalyzed by Maghnite-Na was investigated under suitable conditions. The "Maghnite-Na" is a montmorillonite sheet silicate clay, with exchanged sodium cations to produce Na-Montmor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For the thermogram analysis (TGA) of polyaniline (PANI), it can be found that the weight loss amounted 61, 17% at the temperature range of 187-600°C, which be Composite Materials true because polyaniline it is known a hygroscopic polymer as show in (Figure 9) [42,43]. in the DSC thermogram of the PANI as show in (Figure 10), there were two endothermic peaks at 55.99 and 103.46°C.Therefore, these endothermic peaks were due to the evaporation of water, this is in agreement with the literature [44,45].…”
Section: Thermal Propertiesmentioning
confidence: 95%
“…For the thermogram analysis (TGA) of polyaniline (PANI), it can be found that the weight loss amounted 61, 17% at the temperature range of 187-600°C, which be Composite Materials true because polyaniline it is known a hygroscopic polymer as show in (Figure 9) [42,43]. in the DSC thermogram of the PANI as show in (Figure 10), there were two endothermic peaks at 55.99 and 103.46°C.Therefore, these endothermic peaks were due to the evaporation of water, this is in agreement with the literature [44,45].…”
Section: Thermal Propertiesmentioning
confidence: 95%